DESIGN AND PERFORMANCE OF A 300-WATT HELICAL TYPE H-ROTOR WIND TURBINE - Kurniawati, Diniar Mungil; Farhan, Alfandy Muhammad; Am, Chaerul Qalbi; Gunawan, Gad; Giyantara, Andhika (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The Helical Type H-rotor turbine is a modification of the Darrieus turbine by Alexander Gorlov to improve the design of the H-Darrieus so the turbine can self-starting in low wind speed conditions. The purpose of this study is to analyze the pitch angle (5°, 0°, and -5°) when using the symmetrical airfoil (NACA 0018) on the performance of coefficient of power (CP), tip speed ratio (TSR) and coefficient of torque (CT) produced by Helical Type H-rotor turbine. The method used in this research is experimental investigation using wind tunnel. The Helical Type H-rotor wind turbine is subjected to wind speed of 6 m/s. The results obtained show that the use of 0° pitch angle produces better CP, TSR and CT values than other pitch angles due to the angle of attack produced. this is due to the 0° pitch angle produces an angle of attack that is able to make a more optimal lift force on the turbine blade. At 0° pitch angle the CP value is 0.0337, TSR value is 1.5073 and CT value is 0.0224. While wind turbine that use -5° pitch angle produce better performance than wind turbine that use 5° pitch angle. However, the performance value of both (-5° and 5° pitch angle) is still below the wind turbine with 0° pitch angle.